2022
DOI: 10.2306/scienceasia1513-1874.2022.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of methicillin-resistant Staphylococcus aureus clones: A study at Taksin Hospital, Bangkok, Thailand

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a common pathogen in human diseases. Thirtyseven clinical clones from different patients were tested for a molecular study of the mecA gene and multilocus sequence types (ST). Total genomic extraction, followed by a polymerase chain reaction (PCR) for DNA amplification with specific primers for mecA, and specific primers for various ST were used. Molecular typing for the study of genetic relationships among clones was performed by enterobacterial repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that, compared to methicillin-susceptible Staphylococcus aureus (MSSA), MRSA exhibits higher morbidity, mortality rates, and incurs elevated healthcare costs, posing a significant threat to global public health [ 5 , 6 , 7 ]. According to reports, in many Asian countries, the prevalence of MRSA in hospitals can reach as high as 50–60% [ 8 , 9 ]. In China, despite a recent decline in MRSA incidence, monitoring reports indicate an ongoing prevalence of over 30% annually [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that, compared to methicillin-susceptible Staphylococcus aureus (MSSA), MRSA exhibits higher morbidity, mortality rates, and incurs elevated healthcare costs, posing a significant threat to global public health [ 5 , 6 , 7 ]. According to reports, in many Asian countries, the prevalence of MRSA in hospitals can reach as high as 50–60% [ 8 , 9 ]. In China, despite a recent decline in MRSA incidence, monitoring reports indicate an ongoing prevalence of over 30% annually [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ERIC-PCR is a simple, sharp, and costeffective genotyping technology that discriminates different types of bacterial isolates. The widespread distribution of these repetitive DNA elements of various bacteria should enable the rapid identification of bacterial species and isolates [12][13][14][15], which is useful for the analysis of bacterial genomes [16][17][18][19]. The ERIC sequences can be utilized as efficient primer binding sites in a PCR to produce fingerprints of different bacterial genomes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%